Method overtness, forensic autopsy, and the evidentiary suicide note: A multilevel national violent death reporting system analysis - Rockett, I.; Caine, E.; Stack, S.; Connery, H.; Nolte, K.; Lilly, C.; Miller, Ted; Nelson, L.; Putnam, S.; Nestadt, P.; Jia, H. (Public Library of Science, 2018)
© 2018 Rockett et al. Objective Higher prevalence of suicide notes could signify more conservatism in accounting and greater proneness to undercounting of suicide by method. We tested two hypotheses: (1) an evidentiary suicide note is more likely to accompany suicides by drug-intoxication and by other poisoning, as less violent and less forensically overt methods, than suicides by firearm and hanging/suffocation; and (2) performance of a forensic autopsy attenuates any observed association between overtness of method and the reported presence of a note. Methods This multilevel (individual/county), multivariable analysis employed a generalized linear mixed model (GLMM). Representing the 17 states participating in the United States National Violent Death Reporting System throughout 2011–2013, the study population comprised registered suicides, aged 15 years and older. Decedents totaled 32,151. The outcome measure was relative odds of an authenticated suicide note. Results An authenticated suicide note was documented in 31% of the suicide cases. Inspection of the full multivariable model showed a suicide note was more likely to manifest among drug intoxication (adjusted odds ratio [OR], 1.70; 95% CI, 1.56, 1.85) and other poisoning suicides (OR, 2.12; 1.85, 2.42) than firearm suicides, the referent. Respective excesses were larger when there was no autopsy or autopsy status was unknown (OR, 1.86; 95% CI, 1.61, 2.14) and (OR, 2.25; 95% CI, 1.86, 2.72) relative to the comparisons with a forensic autopsy (OR, 1.62, 95% CI, 1.45, 1.82 and OR, 2.01; 95% CI, 1.66, 2.43). Hanging/suffocation suicides did not differ from the firearm referent given an autopsy. Conclusions Suicide requires substantial affirmative evidence to establish manner of death, and affirmation of drug intoxication suicides appears to demand an especially high burden of proof. Findings and their implications argue for more stringent investigative standards, better training, and more resources to support comprehensive and accurate case ascertainment, as the foundation for developing evidence-based suicide prevention initiatives.